PROGRAM ZIARAH KUBUR SEBAGAI STRATEGI MANAJEMEN PENDIDIKAN KARAKTER DI SMK IT AL-MUSYARROFAH - Nugraha, Ilham (Epistemic: Jurnal Ilmiah Pendidikan, 2026)
This study examines the implementation of a ziarah kubur program as a POAC-based management strategy for character education at SMK IT Al-Musyarrofah, Cianjur. The study aims to explain how planning, organizing, actuating, and controlling are embedded in a routine spiritual program and how the program indicates changes in students’ character. A qualitative case study was employed. Participants included one principal, one vice principal for curriculum, one Islamic education teacher, three supporting teachers, and 156 students from grades X–XII. Informants were selected through a combination of purposive and participatory sampling. Data were collected from September to November 2025 through interviews, observations, reflective journals, attendance records, and school documents. The findings indicate consistent signals of positive character development, particularly in respect toward teachers, reflective awareness of death, and spiritual discipline. Evidence was drawn from interview excerpts, observation notes, and student reflections. This study contributes by mapping POAC steps into a routine spiritual program in an Islamic vocational school and by highlighting the need for structured character evaluation instruments.